(untitled) (Journal of the College of Basic Education, 2022)
Research Summary Research Objective To identify the impact of teaching in the Paksa method in the achievement of first grades teacher students in child health in order to achieve the goal. The researcher put the following hypothesis: - There is no statistically significant difference at the level of significance (0.05) between the average grades Students of the experimental group who studied the Paksa method and the average scores of the control group students who studied in the usual way in the achievement test. The approach adopted experimental research as a research approach appropriate to the research objective and procedures. The experiment was applied to the students of the department of the teacher of the first classes of the morning school, who was intentionally chosen from the departments of the College of Basic Education. Control group studied in the usual way. In order to test the validity of the null hypothesis, the researcher prepared the achievement test, the number of which reached (40) objective paragraphs, and was applied to two exploratory samples other than the basic research sample, the first purpose was to know the clarity of the test paragraphs, determine the time for answering them, and confirm the validity of the test with the agreement of a number of arbitrators, either The second purpose was to extract the psychometric properties of the test. By using the T-test, the researcher obtained the results: The students of the experimental group that studied the Paksa method outperformed the students of the control group who studied in the usual way in the achievement test. The researcher concluded that teaching in the Paksa method has an impact on students’ achievement, as the size of the effect reached (0.28). Accordingly, the researcher put forward a number of recommendations and proposals related to the research results.